Investigating an alternate form of the cognitive reflection test - Thomson, Keela S.; Oppenheimer, Daniel M. (Judgment and Decision Making, 2016)
Much research in cognitive psychology has focused on the tendency to conserve limited cognitive resources. The CRT is the predominant measure of such miserly information processing, and also predicts a number of frequently studied decision-making traits (such as belief bias and need for cognition). However, many subjects from common subject populations have already been exposed to the questions, which might add considerable noise to data. Moreover, the CRT has been shown to be confounded with numeracy. To increase the pool of available questions and to try to address numeracy confounds, we developed and tested the CRT-2. CRT-2 questions appear to rely less on numeracy than the original CRT but appear to measure closely related constructs in other respects. Crucially, substantially fewer subjects from Amazon’s Mechanical Turk have been previously exposed to CRT-2 questions. Though our primary purpose was investigating the CRT-2, we also found that belief bias questions appear suitable as an additional source of new items. Implications and remaining measurement challenges are discussed.